Peran Modalitas Radiologi dalam Deteksi dan Evaluasi Tumor Paru: A Literature Review - Fadilah Alwiyah; Muhammad Ricky Ramadhian (Medula, 2026)
Lung cancer remains one of the leading causes of cancer-related mortality worldwide, making early detection and accurate diagnosis essential for appropriate management. Radiological imaging plays a crucial role in the detection, characterization, and staging of pulmonary tumors. This case report describes the role of radiological modalities in a patient with pulmonary squamous cell carcinoma. A 52-year-old female non-smoker with a history of chronic secondhand smoke exposure for more than 20 years presented with chronic dyspnea, intermittent cough, and significant weight loss. Chest radiography in posteroanterior (PA) and lateral projections revealed a pulmonary mass associated with right upper lobe atelectasis. Further evaluation using contrast-enhanced chest computed tomography (CT) demonstrated a 56.6 × 35.3 mm mass in the apical segment of the right upper lobe, right paratracheal lymphadenopathy, localized right pleural effusion, and findings suggestive of advanced-stage disease. Histopathological examination of tissue biopsy confirmed the diagnosis of right lung squamous cell carcinoma. The patient was subsequently scheduled for chemotherapy with periodic follow-up using chest CT imaging. This case highlights the importance of a multimodal radiological approach in the evaluation of pulmonary malignancies. Chest radiography serves as an effective initial screening and detection tool, whereas contrast-enhanced CT provides superior anatomical detail for lesion characterization, disease staging, biopsy planning, and treatment monitoring. The integration of radiological modalities contributes significantly to comprehensive and accurate management of lung cancer.